Iranian EFL Teachers' and Learners' Perspectives of Oral Error Correction: Does Timeline of Correction Matter? - Ali Akbar Farahani; Soory Salajegheh (Universidad de La Sabana, 2015)
Although the provision of error correction is commonly utilized in education, there are controversies regarding 'when' correction is most effective and why it is effective. This study investigated the differences between Iranian EFL teachers and learners regarding their perspectives towards the timeline of error correction in the speaking skill. Two main categories of immediate and delayed feedback types were determined with the immediate category specifically referring to 'very soon' and 'after speaking' and the delayed one relating to 'after activities' and 'end of class' sub-categories. To empirically test the hypothesis behind the study, a total of 460 teachers and learners were invited to complete Fukuda's questionnaire. The obtained data were analyzed through MANOVA, the results of which showed teachers' preferences towards the immediate correction and the learners' inclination towards the delayed correction. Based on the results, specific properties and circumstances in relation to the timing of feedback were proposed to enhance its efficiency in L2 classrooms.